Cost-effective solar concentrators based on red fluorescent Zn(ii)–salicylaldiminato complex. Issue 21 (11th February 2016) - Minei, Pierpaolo; Fanizza, Elisabetta; Rodríguez, Antonio M.; Muñoz-García, Ana B.; Cimino, Paola; Pavone, Michele; Pucci, Andrea
Abstract : A red light and concentrated zinc complex embedded in PMMA yields a cost-effective and efficient luminescent solar concentrator. Abstract : Sunlight concentration is a promising path to cost-effective photovoltaic (PV) technologies. Compared to standard concentrators based on geometrical optics, luminescent solar concentrators (LSCs) appear to be viable and convenient alternatives because sunlight concentration to PV occurs with diffuse light and there is no need for sun tracking or cooling apparatuses. In this study, we report on the optical efficiencies of luminescent solar concentrators (LSCs) based on poly(methyl methacrylate) (PMMA) thin films doped with a red-emitting zinc(ii ) complex of the D–A–D type ligand N, N ′-bis(2-hydroxy-1-naphthylidene)-diaminomaleonitrile (ZnL). ZnL is attractive for use in LSC owing to its easy and cheap synthesis. ZnL in PMMA shows an emission band at 624 nm, a Stokes shift of 34 nm and an average QY of 23%, data comparable to those recorded in solution and efficiently predicted by DFT calculations. A study of ZnL/PMMA LSC yields optical efficiencies of 7%, which is comparable to those based on the near unity QY fluorophores such as Lumogen Red. These performances were attributed to the higher emission red-shift and larger Stokes shift of ZnL that prevent the loss of efficiencies due to self-absorption and possibly circumvent its lower QY.